Peran Mahkamah Pidana Internasional dalam Genosida Israel terhadap Penduduk Palestina - Hadihartanto, M. Husain; Akbar, M Rizky Fauzian; Luthfiyati, Pefi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One of the international crimes under the authority of the International Criminal Court is genocide. The conflict between Israel and Palestine has been going on for decades and is increasingly leading to acts of genocide from the Israeli side to the Palestinians. Many efforts have been made by the world community as an act of solidarity and siding with Palestine. Efforts are also made by the International Criminal Court to stop the prolonged Israeli-Palestinian conflict. The role of the International Criminal Court is vital in ending the genocide committed by Israel against Palestine, which is increasingly showing its ferocity.